2014
DOI: 10.15252/embr.201438463
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial apoptosis is dispensable for NLRP3 inflammasome activation but non‐apoptotic caspase‐8 is required for inflammasome priming

Abstract: A current paradigm proposes that mitochondrial damage is a critical determinant of NLRP3 inflammasome activation. Here, we genetically assess whether mitochondrial signalling represents a unified mechanism to explain how NLRP3 is activated by divergent stimuli. Neither co-deletion of the essential executioners of mitochondrial apoptosis BAK and BAX, nor removal of the mitochondrial permeability transition pore component cyclophilin D, nor loss of the mitophagy regulator Parkin, nor deficiency in MAVS affects N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
199
5
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(239 citation statements)
references
References 35 publications
24
199
5
6
Order By: Relevance
“…70,71 Interestingly, deletion of caspase-8 in RIP3 knockout bone-marrow-derived macrophages (BMDMs) results in significant reduction of pro-IL-1β and TNF transcription levels, and reduced NALP3 activation following TLR stimulation. Importantly, this role for caspase-8 in the regulation of inflammasome priming is independent of apoptosis 69 and highlights an unexpected role for this caspase in immune homeostasis. Previous studies have also reported an inflammasome-independent role for caspase-8 in inhibiting extensive inflammation in vivo.…”
Section: Caspases In Inflammation and Immunitymentioning
confidence: 93%
See 1 more Smart Citation
“…70,71 Interestingly, deletion of caspase-8 in RIP3 knockout bone-marrow-derived macrophages (BMDMs) results in significant reduction of pro-IL-1β and TNF transcription levels, and reduced NALP3 activation following TLR stimulation. Importantly, this role for caspase-8 in the regulation of inflammasome priming is independent of apoptosis 69 and highlights an unexpected role for this caspase in immune homeostasis. Previous studies have also reported an inflammasome-independent role for caspase-8 in inhibiting extensive inflammation in vivo.…”
Section: Caspases In Inflammation and Immunitymentioning
confidence: 93%
“…Activation of the NALP3 inflammasome only occurs following detection of PAMPs as a second stimulus, and contrary to previous studies, 68 does not involve mitochondrial-mediated apoptosis signaling. 69 Recruitment and activation of caspase-1 by the inflammasome complex is a critical second step in the cleavage and activation of pro-inflammatory cytokines, IL-1β and IL-18, facilitating their secretion and promotion of innate immune responses. Although caspase-1 activation is required to activate inflammatory cytokines, it induces pyroptosis-mediated proinflammatory cell death following acute infection (Figure 3).…”
Section: Caspases In Inflammation and Immunitymentioning
confidence: 99%
“…Recent studies from our laboratory and others demonstrate that mitochondrial dysfunction involving increased mitochondrial ROS production (12,13) and the release of mitochondrial DNA into the cytosol (14) are critical events associated with NLRP3 inflammasome activation. However, recent studies have also suggested that NLRP3 inflammasome activation may occur independently of mitochondrial damage and ROS production, a finding which warrants further investigation (15,16). The integration of metabolic derangements, mitochondrial dysfunction, and inflammasome activation and their contribution to the pathogenesis of sepsis thus remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…It has dual localization on mitochondria and peroxisomes from where it signals different transcriptional programmes. Recent reports implicated MAVS-NLRP3 interaction in localizing NLRP3 to mitochondria for full activation of ASC assembly [50,51]; however, two subsequent reports have been unable to confirm this and further studies are required to clarify its role [52,53].…”
Section: Mitochondrial Antiviral Signalling Protein (Mavs)mentioning
confidence: 97%